DEVELOPING PYTHON PROGRAMMING LANGUAGE SKILLS BASED ON INTERACTIVE METHODS - Mambetkarimov Bayniyaz Meyrmanovich (Scholars Digest Publishing, 2024)
The article deals with the issues of teaching programming languages in higher education, and the author suggests paying special attention to interactive methods. The article discusses the organization of interactive education in higher education institutions, the use of game technologies, the optimal option of the model of interaction between the teacher and the student. The discussion focuses on the problems of teaching programming, for example, the use of interactive methods for each topic, and the creation of a model of a personal learning environment for the teacher and the student. The author recommends to learn Python, one of the interpreted algorithmic programming languages, for teaching programming.
Keywords: education, technology, interactive method, environment, Python, programming, language.